Array comparative genomic hybridisation analysis of boys with X linked hypopituitarism identifies a 3.9 Mb duplicated critical region at Xq27 containing SOX3. Issue 9 (1st September 2004) - Solomon, N M; Ross, S A; Morgan, T; Belsky, J L; Hol, F A; Karnes, P S; Hopwood, N J; Myers, S E; Tan, A S; Warne, G L; Forrest, S M; Thomas, P Q
Abstract : Introduction: Array comparative genomic hybridisation (array CGH) is a powerful method that detects alteration of gene copy number with greater resolution and efficiency than traditional methods. However, its ability to detect disease causing duplications in constitutional genomic DNA has not been shown. We developed an array CGH assay for X linked hypopituitarism, which is associated with duplication of Xq26–q27. Methods: We generated custom BAC/PAC arrays that spanned the 7.3 Mb critical region at Xq26.1–q27.3, and used them to search for duplications in three previously uncharacterised families with X linked hypopituitarism. Results: Validation experiments clearly identified Xq26–q27 duplications that we had previously mapped by fluorescence in situ hybridisation. Array CGH analysis of novel XH families identified three different Xq26–q27 duplications, which together refine the critical region to a 3.9 Mb interval at Xq27.2–q27.3. Expression analysis of six orthologous mouse genes from this region revealed that the transcription factor Sox3 is expressed at 11.5 and 12.5 days after conception in the infundibulum of the developing pituitary and the presumptive hypothalamus. Discussion: Array CGH is a robust and sensitive method for identifying X chromosome duplications. The existence of different, overlapping Xq duplications in five kindreds indicates that X linked hypopituitarism is caused by increased gene dosage. Interestingly, all X linked hypopituitarism duplications contain SOX3 . As mutation of this gene in human beings and mice results in hypopituitarism, we hypothesise that increased dosage of Sox3 causes perturbation of pituitary and hypothalamic development and may be the causative mechanism for X linked hypopituitarism.